ショウワキチ ニ オケル VLF エミッション ノ ハッセイ - 西野, 正徳; ニシノ, マサノリ; 田中, 義人; タナカ, ヨシト; NISHINO, Masanori; TANAKA, Yoshito (国立極地研究所, 1969)
P(論文) 1967年4月から1968年1月まで,昭和基地(地磁気緯度69.7°S)において,VLF帯電磁放射の観測を行なった 受信アンテナは,直交枠形アンテナと垂直アンテナを用いた ここではVLF放射の発生の性格と,他の超高層物理現象との相関について報告する 12kHz帯のVLFの放射は,12月,1月の夏を除いたすべての季節において,夜1800から0100UTに発生した 放射の継続時間は平均して10分から20分が多く,概して地磁気嵐,オーロラ出現,電離層における電波吸収現象と複雑な相関を持っている 一方750Hz帯のVLF放射は,その発生頻度は少ないが,主に昼間に生じた 放射の継続時間は,12kHz帯の放射のそれより長く,大きな地磁気嵐時には,数時間に及ぶものもあった 750kHz帯放射の占有帯域幅の上限はせいぜい4kHz程度であった The observation of VLF emissions has been carried out at Syowa Station (geomagnetic lat. 69.7°S) in the Antarctic from April 1967 to January 1968, using a crossed loop antenna of triangle type and a vertical antenna. In this paper, the occurrence of emissions and their correlation with other geophysical phenomena are discussed. VLF emissions at 12kHz occurred almost always from 1800 to 0100U T in all seasons except for December and January, and the duration of the emissions was 10-20 minutes on the average. VLF emissions at 12kHz showed complicated dependence on geomagnetic disturbances, auroral displays and radio absorptions in the ionosphere. On the other hand, VLF emissions at 750Hz seldom occurred in the daytime, and their duration was longer than that at 12kHz. The occupied highest frequency of such emissions was found to be about 4kHz at most. departmental bulletin paper